The The influence of service quality, store atmosphere, pricefairness and customer satisfaction on consumer loyalty at Sallo Coffee in Jakarta - Hutagalung, Christian Daniel Halomoan; Hutabarat, Zoel (Enrichment : Journal of Management, 2024)
This study aims to analyse whether service quality, store atmosphere, and pricefairness have an influence on customer loyalty either directly or using the customer satisfaction variable as the mediation. This research is quantitative research with a causal approach. The findings of this research aim to benefit the food and beverage industry, particularly the coffee shop company. The sampling procedure was carried out by non-probability sampling with a purposive sampling approach. The total number of respondents used was 225 respondents. The data was processed using SmartPLS version 3.2.9. Based on the test results conducted, it is stated that the service quality and price fairness variables affect customer loyalty. However, the store atmosphere variable has no influence on customer loyalty at Sallo Coffee. while the customer satisfaction variable fails to mediate the three variables with the customer loyalty variable